Propagation of an Endangered Medicinal Plant Species, Celastrus paniculata through Root Cuttings - Sharma, Yashaswini; Venugopal, C. K.; Vasudeva, R.; Manjunath, A. V.; Hegde, Laxminarayan (Indian Forester, 2012)
Investigation was carried out to propagate critically endangered medicinal plant species, Celastrus paniculata by using root cuttings with different growth regulators. The various root and shoot parameters recorded significantly higher in the root cuttings treated with growth regulators as compared to control. The average higher rooting percentage (81.0) was recorded in the cuttings treated with IBA 2000 ppm against control (52.0). The average number of roots per cutting was significantly higher in the cuttings treated with a commercial formulation Quic Root (19.23) followed by IBA 2000 ppm (16.75). The average higher field establishment percentage (95.0) was also observed in IBA 2000 ppm treated cuttings followed by commercial formulation Quic Root treatment. Quic Root was found to be the second best treatment next to IBA 2000 ppm for propagation of C. paniculata through root cuttings.